On the Tannaka group attached to the theta divisor of a generic principally polarized abelian variety - Krämer, Thomas; Weissauer, Rainer (Mathematische Zeitschrift, 2015)
To any closed subvariety Y of a complex abelian variety one can attach a reductive algebraic group G which is determined by the decomposition of the convolution powers of Y via a certain Tannakian formalism.
Gesehen am 19.04.2018